Rent and safety enforcement helmet with telegram bot - Haizal, Hanis Munirah; Sidik, Norbaiti; W Ibrahim, Wan Suhaifiza; Mohd Salleh, Siti Aliyah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project aims to develop a comprehensive smart helmet safety system combining advanced technologies to ensure secure usage and real-time monitoring. The system integrates a Hall effect sensor, magnetic coins, LEDs, Arduino Uno, GPS, ESP32, and a Telegram bot to detect whether the helmet is securely buckled and provide location tracking. The Hall effect sensor identifies the magnetic field from the buckle, triggering LEDs to indicate the status—green for securely fastened and red for unfastened. Additionally, the ESP32 interfaces with a GPS module to track the user's real-time location, sending updates and safety alerts via a Telegram bot. If the helmet is not properly buckled or an emergency occurs, the system notifies the user or concerned personnel. This cost- effective and user-friendly solution demonstrates the potential of IoT and embedded systems to enhance safety for applications in transportation, construction, and sports.